Complex service needs of emerging adults accessing treatment for co-occurring opioid and mental health conditions. Issue 6 (2nd November 2021) - Lombardi, Brianna M.; Greeno, Catherine G.; Jacobs, Leah; Gordon, Jacob; Collins, Kathryn; Jhon, Peter
ABSTRACT: Emerging adults are at high risk for opioid-use disorders (OUDs); however, their service use and co-occurring needs are infrequently described. This study analyzed county-level Medicaid claims across 3 years (2016–2018). A total of 1, 665 individuals aged 17–25 received OUD services. More than 54% of the sample received services for a co-occurring mental health (MH) disorder. Only 21.3% received medications for OUDs (MOUDs), yet those with co-occurring MH were less likely to receive MOUDs and more likely to receive high-intensity services. This article will describe the characteristics of OUD and co-occurring treatment for emerging adults and address implications for social work.